Sindrome de Burnout y Clima Organizacional en Bomberos Voluntarios Trujillo 2011 - Rodríguez Obeso, Regina Lisbeth (2012)
This quantitative research is a descriptive, correlational and cross-section study, which wants to identify the relationship between the Burnout Syndrome and the Organizational Climate Level at the Volunteer Firefighters of Trujillo - 2011. The sample consisted of seventy volunteers firefighters of the “Compañia de Bomberos Salvadora N°26” of Trujillo, selected according to inclusion criteria, who were applied the Maslash Burnout Inventory and the Applied Scale Organizational Climate. The results of both questionnaires were analyzed using SPSS statistical package vs.15.0 and for assessing the relationship between the variables we used the nonparametric statistical Chi-Squared test. About the Burnout Syndrome Dimensions, it was found among the results that the majority of the firefighters have a low level of Emotional Exhaustion (46.8%), a medium level of Depersonalization (34%) and a medium level of Personal Fulfillment (64.4%), and with regard to the Organizational Climate, the most part of the firefighters present a medium level of Organizational Climate (69.4%). Therefore, the conclusion is that there exists a significant relationship between the research variables. Keywords: BurnoutSyndrome, Organizational Climate.